HUBUNGAN MINAT BACA DENGAN KEMAMPUAN MENYEBUTKAN UNSUR INTRINSIK CERITA OLEH SISWA KELAS V SDN 01 WONODADI - Ulfi Nadia Wibowo (Jurnal Guru Kita PGSD, 2018)
Abstract: Relationship in Reading Interest with the Ability to Mention IntrinsicElements of Stories by Class V Students of SDN 01 Wonodadi. The purpose ofthis study was to determine the positive relationship between reading interest and theability to mention intrinsic elements by fifth grade students of SD Negeri 01Wonodadi. This research method is a quantitative type of correlation. Correlationresearch is research conducted by researchers to determine the level of relationshipbetween two or more variables. The study used the type of True ExperimentalDesign type Pretest Posttest Control Group Design. Subjects were students of SDN01 Wonodadi class V, totaling 23 students. Data collection techniques are (1)interview method, (2) questionnaire (3) test. The results of the study of interest inreading multiple choice values on average 78.73 good criteria. The acquisition oflearning outcomes is effective if the average completeness limit is 70.Keyword: Interest in reading, Ability to mention intrinsic elementsAbstrak: Hubungan Minat Baca dengan Kemampuan Menyebutkan UnsurIntrinsik Cerita oleh Siswa Kelas V SDN 01 Wonodadi. Tujuan penelitian iniadalah untuk mengetahui hubungan positif antara minat baca dan kemampuanmenyebutkan unsur intinsik oleh siswa kelas V SD Negeri 01 Wonodadi.MetodePenelitian ini adalah kuantitatif jenis korelasi. Penelitian korelasi adalah penelitianyang dilakukan peneliti untuk mengetahui tingkat hubungan dua variabel atau lebih.Penelitian menggunakan jenis True Experimental Design jenis Pretest PosttestControl Group Design. Subyek adalah siswa SDN 01 Wonodadi kelas V berjumlah23 siswa. Teknik pengumpulan data adalah (1) metode wawancara, (2) angket (3)tes. Hasil penelitian minat baca nilai pilihan ganda rata-rata 78,73 kriteria baik.Perolehan hasil belajar efektif jika batas ketuntasan rata-rata 70.Kata Kunci: Minat baca, Kemampuan menyebutkan unsur intrinsik